The Clinical and Economic Burden of Colorectal Anastomotic Leaks: Middle-Income Country Perspective - Ulysses Ribeiro Jr.; Daiane O. Tayar; Rodrigo A. Ribeiro; Priscila Andrade; Silvio M. Junqueira Jr. (Gastroenterology Research and Practice)
Purpose. Anastomotic leaks (AL) present a significant source of clinical and economic burden on patients undergoing colorectal surgeries. This study was aimed at evaluating the clinical and economic consequences of AL and its risk factors. Methods. A retrospective cohort study was conducted between 2012 and 2013 based on the billing information of 337 patients who underwent low anterior resection (LAR). The outcomes evaluated were the development of AL, use of antibiotics, 30-day readmission and mortality, and total hospital costs, including readmissions and length of stay (LOS). The risk factors for AL, as well as the relationship between AL and clinical outcomes, were analyzed using multivariable Poisson regression. Generalized linear models (GLM) were employed to evaluate the association between AL and continuous outcomes (LOS and costs). Results. AL was detected in 6.8% of the patients. Emergency surgery (aRR 2.56; 95% CI: 1.15–5.71, p=0.021), blood transfusion (aRR 4.44; 95% CI: 1.86–10.64, p=0.001), and cancer diagnosis (aRR 2.51; 95% CI: 1.27–4.98, p=0.008) were found to be independent predictors of AL. Patients with AL showed higher antibiotic usage (aRR 1.69; 95% CI: 1.37–2.09, p<0.001), 30-day readmission (aRR 3.34; 95% CI: 1.53–7.32, p=0.003) and mortality (aRR 13.49; 95% CI: 4.10–44.35, p<0.001), and longer LOS (39.6 days, as opposed to 7.5 days for patients without AL, p<0.001). Total hospital costs amounted to R$210,105 for patients with AL in comparison with R$34,270 for patients without AL (p<0.001). In multivariable GLM, the total hospital costs for AL patients were 4.66 (95% CI: 3.38–6.23, p<0.001) times higher than those for patients without AL. Conclusions. AL leads to worse clinical outcomes and increases hospital costs by 4.66 times. The risk factors for AL were found to be emergency surgery, blood transfusion, and cancer diagnosis.